AB0501 THREE CASES OF VERTEBRAL ARTERITIS IDENTIFIED ON FDG-PET IN PATIENTS WITH SUSPECTED GCA AT UNIVERSITY COLLEGE LONDON HOSPITAL (UCLH). (2nd June 2020) - Ludwig, D.; Naja, M.; Voo, S.; Morris, V.
Abstract : Background: Giant cell arteritis (GCA) may affect both cranial and extra-cranial vessels; where the latter occurs, it can be termed large-vessel GCA (LV-GCA). Large vessel involvement is common: histological evidence has been seen in 80% of autopsies of patients with known GCA, and imaging studies suggest large vessel involvement in over 80% 1 . LV-GCA is important to diagnose due to the risks of vascular complications such as occlusion and ischaemic stroke. The clinical diagnosis can be challenging, and the American College of Rheumatology (ACR) GCA classification criteria often underperform in cases of LV-GCA 1 . F-fluorodeoxyglucose positron emission tomography (FDG-PET) has been found to be useful in the detection of extra-cranial involvement to support the diagnosis of LV-GCA. 2 Objectives: To appreciate the variability in presentation of cases of LV-GCA, and to further characterise a subgroup of patients with vertebral arteritis. To explore the use of FDG-PET imaging in GCA patients in addition to or in place of traditional diagnostic tools (temporal artery ultrasound / biopsy). Methods: Through evaluation of the new GCA fast-track pathway implemented at UCLH, a subgroup of patients diagnosed with vertebral arteritis was identified. The history and presentation of these patients were analysed. Results: Three patients were diagnosed with vertebral arteritis. All three were male, Caucasian and aged over 70. All were investigated for GCA due to a history of severe headache (frontal in one, occipital in one, bi-temporal in one) with associated red flag symptoms. Two had a history of jaw claudication and visual disturbances (unilateral visual loss in one, transient diplopia in the other). Both of these patients had positive temporal artery biopsies. The third patient had no ischaemic symptoms but a strong history of prominent polymyalgic features and a positive temporal artery ultrasound. Inflammatory markers were raised in two, and normal in one, of the patients. Only one had systemic symptoms (weight loss). All three proceeded to FDG-PET scans which showed vertebral arteritis and were commenced on immunosuppressive treatment. Conclusion: The cases discussed illustrate the heterogeneity of the presentation of LV-GCA, and the diagnostic challenge this poses. FDG-PET imaging is useful in confirming extra-cranial involvement and therefore guiding treatment. References: [1] Large-vessel giant cell arteritis: diagnosis, monitoring and management. Matthew J Koster, Eric L Matteson, Kenneth J Warrington. 2018, Rheumatology, Vol. 57, pp. 32-42. [2] EULAR recommendations for the use of imaging in large vessel vasculitis in clinical practice. Dejaco C, Ramiro S, Duftner C, et al. 2018, Annals of the Rheumatic Diseases, Vol. 77, pp. 636-643. Disclosure of Interests: None declared